Effect of Fare, Service Quality, and Baggage Handling on Passenger Satisfaction - Ahmad Bahrawi; Sri Rahayu Surtiningtyas; Ridho Rinaldi; Meita Maharani Sukma; Lusiana Dewi Kusumayati; Lady Silk Moonlight (Universitas Trunodjoyo Madura, 2025)
Ensuring client satisfaction is a crucial aspect of the aviation industry that determines the success of airline operations. To retain and attract customers, airlines must provide services that encourage loyalty and appeal to potential passengers, such as those of Garuda Indonesia Airlines. Several factors influence customer satisfaction, including ticket fares, service quality, and baggage handling. This study aims to examine the extent to which these three variables affect the satisfaction levels of Garuda Indonesia passengers departing from Juanda International Airport, Surabaya. A quantitative strategy was used, and information was gathered using a Likert-scale questionnaire. After removing outliers, 96 valid responses were analyzed. The three variables have a considerable impact on passenger satisfaction, as demonstrated by the regression analysis’s 90.8% Adjusted R Square result. In comparison, the remaining 9.2% is explained by additional elements not covered in this research. The results are expected to serve as recommendations for evaluating and improving Garuda Indonesia’s service performance at Juanda International Airport. Overall, this research contributes to enhancing airline strategies aimed at maximizing service effectiveness, strengthening competitiveness in the aviation sector, and expanding academic understanding of the connection between flight fares, service quality, baggage handling, and customer satisfaction.